Evaluation of Performance Appraisal System in Public Sector Universities: A Critical Case of a Public Sector Institution (PSI) - RABIA INAM KHAN; MUHAMMAD NISAR KHAN; MUHAMMAD ILYAS (Journal of Business & Tourism, 2021)
The utmost aim of this research is to examine the current performance evaluation system undertaken by a public sector university and to uncover the perceptions of teachers about the existing system and to present some recommendations to perk up the system. This research is an exploratory study where primary data has been collected from a wellrecognized public sector university through questionnaires. 344 questionnaires were distributed out of which 300 were returned. Findings of the study depict that the current evaluation system does not provide feedback to the teachers. The results of the appraisal reports are kept confidential which becomes a hurdle in teachers’ developmental process. In addition to it, results have showed that performance appraisal system have impact on teachers’ commitment and their skills. This study can play a crucial role in coercing the higher authorities to contemplate their performance evaluation system. This study suggests that by setting mutual performance objectives, emphasizing on performance planning, and providing feedback to the teachers’ can help in learning and development purposes of teachers in universities.